2018
DOI: 10.22175/mmb2017.04.0023
|View full text |Cite
|
Sign up to set email alerts
|

Modified Atmosphere Packaging Improves Surface Color of Dark-Cutting Beef

Abstract: Abstract:The objective was to determine the effects of modified atmosphere packaging (MAP) on the surface color of darkcutting beef that had been aged for 21 d. The USDA Choice (normal-pH; IMPS #180) strip loins (n = 10) and no-roll dark-cutter strip loins (n = 10) were obtained from a commercial packing plant within 72 h of harvest. Both normal-pH and dark-cutting beef were vacuum packaged and aged for 21 d. Steaks were cut from both normal and dark-cutting loins, assigned to 1 of 3 packaging treatments; PVC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Preharvest stress can decrease glycogen content in muscles, hence limited lactic acid is formed postmortem. Previous studies have also reported greater pH in dark-cutting beef ( Sawyer et al, 2009 ; Mitacek et al, 2018 ). A greater pH can increase cell swelling or fiber width ( Barbut et al, 2005 ; Hughes et al, 2017 ), which can decrease light reflectance and oxygen diffusion into the meat.…”
Section: Resultsmentioning
confidence: 71%
“…Preharvest stress can decrease glycogen content in muscles, hence limited lactic acid is formed postmortem. Previous studies have also reported greater pH in dark-cutting beef ( Sawyer et al, 2009 ; Mitacek et al, 2018 ). A greater pH can increase cell swelling or fiber width ( Barbut et al, 2005 ; Hughes et al, 2017 ), which can decrease light reflectance and oxygen diffusion into the meat.…”
Section: Resultsmentioning
confidence: 71%
“…Previous research also reported lower L* (darker color) values in dark-cutting beef. Increased pH can enhance oxygen consumption and metmyoglobin reducing activity of dark-cutting beef in comparison to normal-pH beef. , Ashmore et al noted that, in experimentally induced dark-cutting conditions by injecting epinephrine, there were no significant differences in the mitochondrial content. However, limited research has compared the mitochondrial content in dark-cutting (that has not been experimentally induced) and normal-pH beef.…”
Section: Discussionmentioning
confidence: 95%
“…Dark-cutting steaks in high-oxygen and carbon monoxide modified atmosphere packages had greater redness than steaks in polyvinyl chloride (PVC) (Wills et al, 2017;Mitacek et al, 2019;Zhang et al, 2018;Ramanathan et al, 2019). Greater lipid oxidation (Mitacek et al, 2018) and consumer safety concerns (Grebitus et al, 2013) limit the application of highoxygen and carbon monoxide modified atmosphere packaging, respectively, at the retail level.…”
Section: Introductionmentioning
confidence: 99%